Native American "Deaths of Despair" and Economic Conditions - Randall K. Q. Akee; Donn. L. Feir; Marina Mileo Gorzig; Samuel Myers Jr (Institute of Labor Economics (IZA), 2022)
Non-Hispanic whites who do not have a college degree have experienced an increase in "deaths of despair" – deaths caused by suicide, drug use, and alcohol use. Yet, deaths of despair are proportionally largest among Native Americans and the rate of increase of these deaths matches that of non-Hispanic white Americans. Native American women and girls face the largest differentials: deaths of despair comprise over 10% of all deaths among Native American women and girls – almost four times as high as the proportion of deaths for non-Hispanic white women and girls. However, the factors related to these patterns are very different for Native Americans than they are for non-Hispanic white Americans. Improvements in economic conditions are associated with decreased deaths from drug use, alcohol use, and suicide for non-Hispanic white Americans. On the other hand, in counties with higher labor force participation rates, lower unemployment, and higher ratios of employees to residents, there are significantly higher Native American deaths attributed to suicide and drug use. These results suggest that general improvements in local labor market conditions may not be associated with a reduction in deaths of despair for all groups.
Keywords: I14; J15; J16; 330; Native American; public health; deaths of despair; economic conditions